Eco-design of nanostructured cellulose sponges for sea-water decontamination from heavy metal ions. (10th February 2020) - Fiorati, Andrea; Grassi, Giacomo; Graziano, Aurora; Liberatori, Giulia; Pastori, Nadia; Melone, Lucio; Bonciani, Lisa; Pontorno, Lorenzo; Punta, Carlo; Corsi, Ilaria
Abstract: The growing human activity on the sea coasts is more and more associated to a progressively increasing of seawater pollution. Ship operational discharges (such as bilge water), together with local accidents or illegal activities, often lead to detect ppm concentrations of heavy metal ions in marine waters. For this reason, highly efficient remediation technologies are required to guarantee the abatement of these contaminants. The use of engineered nanomaterials (ENMs) is emerging as a valuable alternative for environmental remediation. However, the concerns related to ENMs potential ecotoxicity still limit their use in real scenarios, in spite of the good to excellent remediation performances. The correct choice of the starting material and of the synthetic protocol could provide new safe-by-design solutions for this purpose. Following this approach, we herein report the eco-design strategy used for the development of eco-friendly cellulose-based nanostructured sponges (CNS). The latter resulted to be effective sorbent units for heavy metals removal from seawater. The materials were obtained following a two-step protocol, consisting first in the production of TEMPO-oxidized cellulose nanofibers, followed by their cross-linking in the presence of branched polyethyleneimine. CNSs herein described exhibit high performances in removing a wide range of heavy metal ions (Zn(II), Cd(II), Cr(III), Hg(II), Ni(II), and Cu(II)) from artificial sea water (ASW) in a concentration range of 1–250 ppm. Environmental safety of materials (ecosafety) was investigated by using a standardized ecotoxicity bioassay as algal growth inhibition test (OECD 201) coupled with an in vivo exposure study using a filter-feeder marine bivalve species in which immune cells viability (neutral red retention time) and genotoxicity (micronucleus test) were investigated. The results in terms of eco-safety evaluation led to the optimization of the material synthetic strategy (eco-design) and allow to combine the best decontamination efficiency with no risk for aquatic biota. Graphical abstract: Image 1 Highlights: Synthesis of cellulose nanosponges is simple, cheap, and scalable. Eco-design of materials follows a step by step environmental safety assessment. Materials show superb adsorption performances of transition metals from sea water. Ecotoxicological validation in realistic scenarios limits risk for aquatic biota.